An epidemiologic analysis of Candida spp. urinary infections in intensive care unit - Ekşi, Fahriye (2022)
Background and objectives: The finding of Candida species in urine is an usual finding and is called candiduria. There is an increase in the frequency of urinary tract infections (UTI) caused by Candida especially in critically ill patients. This study aimed to determine the epidemiological, clinical, and mycological characteristics of Candida urinary infections in intensive care unit (ICU) and antifungal susceptibilities. Methods: Urine cultures of 394 ICU patients with clinical suspicion of UTI were evaluated. After 24-48 hours of incubation, colonies appeared to grow as yeast, were morphologically examined by Gram staining. Candida strains that grew 104 ≥ CFU/mL in urine cultures were accepted as candiduria. The susceptibilities of the Candida strains to amphotericin B, itraconazole, fluconazole, voriconazole, flucytosine, and caspofungin were investigated with broth microdilution method. Results: The distribution of the isolated 100 urinary Candida strains were as, 54 Candida albicans, 34 C. glabrata, 7 C. tropicalis, 2 C. kefyr, 2 C. lusitaniae, and 1 as C. parapsilosis. Among 100 Candida species isolated in our study susceptibility rates of amphotericin B, flucytosine, caspofungin, fluconazole, itraconazole, and voriconazole were 100%, 100%, 91%, 23%, 13%, 25.8%, respectively. Conclusion: Accurate identification of Candida spp., as well as the investigating the antifungal susceptibility, will be beneficial in terms of the effectiveness of the treatment and the prevention of resistance development.